2016
DOI: 10.1097/qai.0000000000001043
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital is Associated With Late HIV Diagnosis: An Ecological Analysis

Abstract: Background Late HIV diagnosis is associated with higher medical costs, early mortality among individuals, and HIV transmission in the population. Even under optimal configurations of stable or declining HIV incidence and increase in HIV case findings, no change in proportion of late HIV diagnosis is projected after year 2019. We investigated the association among social capital, gender, and late HIV diagnosis. Methods We conduct ecological analyses (ZIP code, N=166) using negative binomial regression of gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 62 publications
7
39
0
Order By: Relevance
“…The direction found in this study is similar to the direction found by Ransome, Galea and Pabayo et al among men [85], measured by a civic engagement indicator that includes a component of participating in local organizations, just as in this study. While in general, social capital would be expected to be associated with lower late HIV diagnosis, the directions found in these two studies may indicate a complex pattern more detailed data are required to answer.…”
Section: Discussionsupporting
confidence: 89%
“…The direction found in this study is similar to the direction found by Ransome, Galea and Pabayo et al among men [85], measured by a civic engagement indicator that includes a component of participating in local organizations, just as in this study. While in general, social capital would be expected to be associated with lower late HIV diagnosis, the directions found in these two studies may indicate a complex pattern more detailed data are required to answer.…”
Section: Discussionsupporting
confidence: 89%
“…We observed in our study that income inequality and socioeconomic deprivation was associated with higher rates of late HIV diagnosis but only in crude models, not adjusted for covariates. The direction of association was consistent with crude results from one study that examined HIV incidence (Buot et al, 2014), one study that examined AIDS mortality rates among injection drug users (Friedman et al, 2013), and multivariable results from one study that examined late HIV diagnosis based on 2005–6 HIV data (Ransome et al, 2016). …”
Section: Discussionsupporting
confidence: 68%
“…In contrast, in multivariable models; for women compared to men, black racial concentration appeared to have a larger magnitude of association on late HIV diagnosis. One ecological study in NYC based on late HIV diagnosis data from 2005 to 2006 also found the same pattern of association between black racial concentration and late HIV diagnosis for women compared to men (Ransome et al, 2016). …”
Section: Discussionmentioning
confidence: 76%
“…Thus, we cannot generalize the findings to other indicators such as social cohesion or collective efficacy. However, in previous HIV and social capital research, social/civic/political participation was highly positively correlated with other social capital indicators such as collective efficacy, social cohesion, and informal social control [32] . We also could not analyze participation by the type of organizations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The preponderance of evidence documenting a protective association between social capital and HIV risks and HIV care continuum outcomes has been among international populations [25, 2731] and there are only a handful of ecological studies on the topic in the US [3235] . One state-level ecological study using data from year 1999 showed that higher social capital was associated with lower AIDS case rates [34] .…”
Section: Introductionmentioning
confidence: 99%